Just Transition - COP29 Negotiation Updates - Koren, Judith; Rabago, Laura (2024)
The just transition centers on shifting to a low-carbon economy in a way that supports affected workers, communities, and industries, ensuring social equity and environmental sustainability. The IPCC stresses that the just transition requires targeted and proactive measures from government and relevant actors to reduce any negative social, environmental or economic impacts of economy-wide transitions. The just transition means different things to different groups, underscoring the importance of an inclusive, diverse multi-stakeholder approach to categorically ensure no one is left behind. Originating from labor movements in North America in the 1970s, it has developed as a central piece in the energy transition, highlighting the need for fair job creation, worker protections, reskilling, and social dialogue, particularly in sectors heavily impacted by decarbonization, such as coal and other fossil fuels.